Processing of conductive filled polymers using microinjection - Pereira, A. G. (2011)
Polystyrene granules were coated by sputtering with an innovative film of stainless steel obtaining this way a composite. To compare results it was necessary to prepare two different composites, mixing polymer granules with steel fibers mechanically in a drum. Microinjection molding is a processing technique that allowed obtaining a representative sample of each composite. Scanning electron microscope (SEM) allowed the characterization of the coating thickness while the dispersion and distribution of metal particles were analyzed by optical microscopy in polarized light. Results showed a uniform thickness of the coating and good dispersion of the reinforcements in the matrix. Electrical and mechanical properties of the composites were characterized by measuring the electrical resistivity and flexural tests. Considerable values of conductivity were exhibited in composites with carbon nanotubes and a slight increase in the modulus of the polymers due to reinforcement incorporation was noticed.